Wear and corrosion behaviors of high-power laser surface-cleaned 304L stainless steel - Park, Hyoungwon; Jong Yoo, Hyun; Park, Changkyoo (Optics and Laser Technology, 2024)
In this study, the influence of laser surface cleaning (LSC) on the wear and corrosion behaviors of 304L stainless steel (SS304L) is discussed. A kilowatt-level (1140 W) Nd:YAG laser with different hatch distances and repetition times is applied to remove the corrosion layer of SS304L, and its corresponding effects on SS304L are examined. Electron backscatter diffraction (EBSD) and kernel average misorientation (KAM) analyses of LSC-induced microstructural modifications reveal a smaller grain size and larger strain rate after the LSC process. In addition, an electron probe X-ray microanalyzer (EPMA) confirms the remaining local Cr-depletion regions even after a complete corrosion layer removal. These Cr-depletion regions are developed during the corrosion process, and an additional LSC process significantly reduces the Cr-depletion regions. Electrochemical tests are conducted to examine the corrosion behavior of the base metal and LSC specimens, and a larger corrosion resistance is achieved with fewer local depletion regions. Moreover, tribological tests reveal that a higher wear resistance is achieved after the LSC process owing to an increase in the surface microhardness.
CRIS-Team Scopus Importer:2023-08-11
Keywords: 304L stainless steel; Corrosion; Corrosion removal; Laser surface cleaning; Tribology